Nitrogen-doped carbon-coated molybdenum compound with heterostructure as well as preparation method and application of nitrogen-doped carbon-coated molybdenum compound
By constructing a nitrogen-doped carbon-coated heteromolybdenum compound structure on the positive electrode support of the lithium-sulfur battery, the problems of poor conductivity, volume expansion and shuttle effects of lithium-sulfur battery are solved, and higher cyclic stability and redox kinetic performance are achieved.
Patent Information
- Application Number
- CN202411943644.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Lithium-sulfur batteries have problems such as poor conductivity, severe volume expansion and lithium polysulfide shuttle effect, resulting in poor circulation stability and low utilization rate of active substances.
By constructing nitrogen-doped carbon-coated molybdenum compounds with heterostructure on the positive electrode support, the coupling effect between heterointerfaces and built-in electric field is used to improve the adsorption and catalytic activity of lithium polysulfide, reduce the shuttle effect, and protect the heterostructure through carbon coating.
The cycle stability and redox kinetic performance of lithium-sulfur batteries are significantly improved, the cycle life of the battery is extended, and the volume expansion during charging and discharging is suppressed.
Smart Images

Figure CN119786587A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-sulfur battery positive electrode carrier and catalytic technology, and in particular to a nitrogen-doped carbon-coated molybdenum compound with a heterogeneous structure, and a preparation method and application thereof. Background Art
[0002] Lithium-sulfur batteries have an ultra-high theoretical capacity (1675mAh g -1 ) and energy density (2600W h kg -1 ), however, lithium-sulfur batteries have the following three basic problems: poor conductivity of the positive electrode active material, severe volume expansion during charge and discharge, and the shuttling problem of soluble lithium polysulfide formed by multi-step reactions in the electrolyte. Using carbon or modified carbon as the positive electrode carrier material of lithium-sulfur batteries can effectively solve the problems of poor conductivity and volume expansion of active sulfur, but the shuttling problem is the main reason for the decline in cycle stability, low utilization of active materials, and poor redox kinetics of lithium-sulfur batteries.
[0003] In order to solve the problem of poor cycle stability of lithium-sulfur batteries due to the shuttle effect, transition metal oxides can be loaded on the positive electrode carrier, and the polarity of transition metal oxides and LiPSs can be used to effectively adsorb LiPSs in the electrolyte, thereby reducing the concentration of long-chain LiPSs in the electrolyte, and finally achieving the effect of inhibiting the "shuttle effect". For example, the existing document 1 (KIM WI, YEON JS, PARK H, et al. Polyoxometalate derived hierarchically structured N, P-Codoped reduced grapHene oxide / MoO2 composites for high performance lithium-sulfur batteries [J]. Composites Part B: Engineering, 2023.) prepared a composite material of N, P co-doped rGO and MoO2 derived from a polyoxometalate hierarchically structured structure. After being used as the positive electrode of a lithium-sulfur battery, the initial specific capacity was 1098.5 mAh g at 0.2C. -1, 82.2% high capacity retention rate and only 0.082% decay rate per cycle. This technical solution uses the polarity of MoO2 to achieve the adsorption of LiPSs, significantly reducing the shuttling of LiPSs and achieving the technical effect of improving cycle stability. However, due to the low catalytic performance of the transition metal oxide MoO2, after adsorbing LiPSs, LiPSs cannot be converted into Li2S. At the same time, due to the excessive polarity of MoO2, the desorption conversion of LiPSs is affected, thus significantly reducing the redox kinetics of the reaction.
[0004] In order to improve the redox kinetics of LiPSs in lithium-sulfur batteries, transition metal sulfides can be used for catalysis to improve the bidirectional conversion efficiency of LiPSs and the final product Li2S. For example, the existing literature 2 (RAZAQ R, ZHANGN, XIN Y, et al. Dense MoS2 Micro-Flowers Planting on Biomass-Derived Carbon Fiber Network for Multifunctional Sulfur Cathodes [J]. Chemistry Select, 2020.) assembled dense MoS2 microflowers MoS2 / CFs as lithium-sulfur battery cathodes by planting cross-linked two-dimensional MoS2 nanosheets on biomass-derived carbon fiber networks. The initial specific capacity is 1149 mAh g at 0.2C. -1 The specific capacity at 4C is 608 mAh g -1 , and has good rate performance. This technical solution accelerates the bidirectional conversion of LiPSs and Li2S by cross-linking MoS2 on biomass carbon to form a nanoflower structure, thereby improving the redox kinetics. However, transition metal sulfides have poor polarity to LiPSs. During the continuous reaction process, they cannot effectively anchor free LiPSs, resulting in LiPSs deposition on the negative electrode surface during the cycle, even if the negative electrode is passivated, ultimately reducing the cycle stability. Therefore, adding only transition metal sulfides cannot achieve the adsorption effect of LiPSs.
[0005] In order to solve the problem of improving the adsorption capacity and catalytic activity of LiPSs at the same time, metal oxides with strong polarity and metal sulfides with strong catalytic properties can be prepared into heterostructures, so that the material has both the adsorption capacity and catalytic activity for LiPSs. In addition, the presence of heterointerfaces can accelerate the transfer of electrons and further improve the performance. For example, the existing document 3 (ZHANG T, ZHAC, LIU S, et al. Boosting the polysulfide conversion by VO2-VS2 heterostructure for lithium-sulfur batteries [J]. Journal of Alloys and Compounds, 2023.) uses a two-step hydrothermal method to synthesize the VO2-VS2 heterostructure. Under 0.2C conditions, the initial discharge capacity is as high as 1236 mAh g -1 Even at 1C, the battery capacity remains stable at 432 mAh g after 500 cycles. -1 . This technical solution generates a built-in electric field at the interface of the two phases by constructing a VO2-VS2 heterostructure, and improves the adsorption of LiPSs by increasing the interface polarity. At the same time, the uneven charge force field at the interface of the heterostructure is used to accelerate the transmission of electrons, thereby accelerating the adsorption-diffusion-conversion process of LiPSs at the interface, that is, improving the cycle stability and reaction rate at the same time. However, since the active substance sulfur still has severe volume expansion during the charge and discharge process, the heterostructure is destroyed, especially at the interface of the heterostructure. Therefore, the collapse of the heterostructure leads to the disappearance of the effect of improving the cycle stability and reaction rate.
[0006] In order to suppress the volume change during the charge and discharge process, nitrogen-doped porous carbon materials can be coated on the heterostructure to achieve the effect of suppressing volume expansion and protecting the heterostructure. At the same time, the conductivity of the carbon material itself is used to improve the conductivity of the heterostructure. For example, the existing document 4 (Xu Fen, Shi Bin, Sun Lixian, et al. A spherical carbon-coated ZnO-ZnS heterostructure material and its preparation method and application [P]. Guangxi Zhuang Autonomous Region: CN202410097707.2, 2024-04-26.) synthesized a spherical carbon-coated ZnO-ZnS heterostructure material by two hydrothermal methods. At a current density of 0.1C, the initial specific capacity is 1200-1400mAh g -1,Under the condition of 100 cycles, the capacity retention rate is a high capacity retention rate of 75-80%. This technical solution effectively protects the morphology of the heterostructure by carbonizing and coating the heterostructure with polydopamine, and the carbonized carbon layer can improve the conductivity of the heterostructure. However, in the case of Zn transition metal compounds with carbon-coated spherical structures, the carbon-coated spherical structure only reacts with LiPSs on the surface, and the active sites inside cannot be exposed, that is, there are fewer active sites, and both ZnO and ZnS are wide bandgap semiconductors. Electrons need to overcome a large energy barrier during transmission, and cannot effectively accelerate the reaction. Summary of the invention
[0007] The purpose of the present invention is to provide a nitrogen-doped carbon-coated molybdenum compound with a heterogeneous structure and a preparation method and application thereof.
[0008] The basic principle involved in the present invention is to enhance the binding force between materials through atomic-level coupling between heterogeneous interfaces in heterogeneous structures, form a charge difference at the interface, accelerate the transmission of electrons and ions in the entire electrocatalytic process, and improve the cyclic stability of the reaction and the redox bidirectional catalytic rate.
[0009] In order to obtain the above effects, that is, the technical problem to be solved by the present invention, a heterostructure is constructed by vapor deposition. The specific method is to control the sulfurization and deposit on the molybdenum precursor to achieve partial sulfurization to form a heterostructure.
[0010] Among them, polydopamine is carbonized to form a carbon layer covering the surface of the heterostructure during the vapor deposition process, thereby improving the structural stability and conductivity of the heterostructure;
[0011] By utilizing the metallic properties of MoO2 to improve the conductivity of the heterostructure, the polarity of the transition metal oxide can anchor LiPSs, and then utilizing the high catalytic activity and flaky structure of MoS2 to increase the specific surface area of the entire heterostructure, increase the active sites, and accelerate the bidirectional redox rate;
[0012] MoO2 and MoS2 have a low bandgap and low energy required for electron transition, which can effectively accelerate the reaction. The built-in electric field characteristics of the heterostructure reduce the reaction energy barrier and further accelerate the transmission of electrons.
[0013] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:
[0014] A nitrogen-doped carbon-coated molybdenum compound with a heterogeneous structure, using ammonium molybdate tetrahydrate as a molybdenum source and thioacetamide TAA as a sulfur source, firstly, obtaining a polydopamine-coated precursor PDA / Mo by stirring precipitation, then calcining the precursor and TAA, and performing partial sulfurization, to obtain a nitrogen-doped carbon-coated molybdenum compound with a heterogeneous structure NC / MoS2-MoO2, referred to as NC / MSO; the NC / MSO is composed of MoO2 and MoS2, and there is a heterogeneous interface between MoO2 and MoS2; the carbon layer of the NC / MSO has a defect peak D peak and a graphite peak G peak, and the peak height ratio I D / I G =0.847; the microstructure of NC / MSO is a spherical structure formed by stacking layers, and the surface of the layers is rough; there are obvious gaps between the layers.
[0015] A method for preparing a nitrogen-doped carbon-coated molybdenum compound having a heterogeneous structure comprises the following steps:
[0016] Step 1, preparation of a dopamine-coated molybdenum compound precursor, first, dissolving ammonium molybdate tetrahydrate in a mixed solvent to obtain an ammonium molybdate solution, and at the same time, placing dopamine hydrochloride in deionized water and ultrasonically obtaining a dopamine solution; then, under certain conditions, slowly dropping the dopamine solution into the ammonium molybdate solution for mixing and stirring to obtain a reaction solution, after the dropwise addition is completed, under certain conditions, stirring the reaction solution for reaction, after the reaction is completed, filtering the obtained red suspension and freeze-drying it to obtain a dopamine-coated molybdenum compound precursor PDA / Mo, referred to as PDA / Mo;
[0017] In the step 1, the mass ratio of ammonium molybdate tetrahydrate to dopamine hydrochloride is 2.13:1;
[0018] In step 1, the mixed solvent is a mixed solution of ethanol, deionized water and ammonia water, wherein the volume ratio of ethanol, deionized water and ammonia water is 20:10:1;
[0019] In step 1, the mixing and stirring conditions are as follows: adding dropwise under stirring, the mixing and stirring temperature is 50-60°C, the mixing and stirring time is 0.5-1h, and the dropping rate is 1mLmin -1 The addition time is 10-15min;
[0020] In step 1, the stirring reaction conditions are: pH value is 8.5-9, reaction temperature is room temperature, and reaction time is 10-12h;
[0021] Step 2, preparation of nitrogen-doped carbon-coated molybdenum compounds with heterostructures. Under certain conditions, the PDA / Mo obtained in step 1 and thioacetamide TAA meet a certain mass ratio, and TAA and PDA / Mo are calcined to obtain nitrogen-doped carbon-coated molybdenum compounds with heterostructures NC / MoS2-MoO2, referred to as NC / MSO.
[0022] In the step 2, the mass ratio of PDA / Mo to thioacetamide TAA is 1:1;
[0023] In step 2, the calcination conditions are as follows: TAA is placed at the upwind port, PDA / Mo is placed at the downwind port, and the argon gas flow rate is 40-60 ml min -1 , heating rate is 2-5℃min -1 , the calcination temperature is 700-800℃, and the calcination time is 3-6h;
[0024] When nitrogen-doped carbon-coated molybdenum compounds with heterostructures are used as positive electrode materials for lithium-sulfur batteries, the initial discharge capacity is 1100-1200 mAh g at a current rate of 0.2C. -1 The nitrogen-doped carbon-coated molybdenum compound having a heterogeneous structure is characterized in that: under the condition of 200 cycles, the residual discharge capacity is 800-900 mAhg -1 , the capacity retention rate is 75-80%.
[0025] The technical effects of the present invention have been tested experimentally, and the specific contents are as follows:
[0026] The characteristics and functions of the nitrogen-doped carbon-coated MoS2-MoO2 heterostructure material obtained by the method of the present invention were experimentally tested, and the results are as follows:
[0027] XRD detection shows that NC / MoS2-MoO2 contains both the characteristic peaks of monoclinic MoO2 and 2H hexagonal MoS2.
[0028] SEM examination shows that NC / MoS2-MoO2 is a spherical structure of stacked sheets, and the sheets are covered with carbon layers.
[0029] EDS detection shows that NC / MoS2-MoO2 contains Mo, O, S, C, and N elements at the same time, and the elements are evenly distributed.
[0030] Raman spectroscopy shows that the carbon layer of NC / MSO has obvious defect peak D peak and graphite peak G peak, and the peak height ratio I D / I G=0.847, indicating that the carbonized PDA carbon layer has abundant defects and a high degree of graphitization, that is, it has excellent pore structure and good electrical conductivity.
[0031] TEM detection shows that: NC / MSO has lattice fringes of MoO2 and MoS2 at the same time, and there is a heterogeneous interface, that is, a heterogeneous structure is formed by MoO2 and MoS2; the lattice fringes spacing between MoO2 is 0.240nm; the lattice fringes spacing between MoS2 is 0.615nm, which proves the formation of a heterogeneous structure of NC / MoS2-MoO2.
[0032] The constant current cycle charge and discharge test results show that under the condition of current rate of 0.2C, the initial discharge capacity is 1100-1200mA hg -1 ; Under the condition of 200 cycles, the residual discharge capacity is 800-900mA hg -1 , the capacity retention rate is 75-80%.
[0033] The results of cyclic voltammetry tests show that there is one oxidation peak and two reduction peaks in the spectrum, indicating that the battery has good redox performance and good reaction reversibility. After three cycles, the peaks basically overlap, indicating that the battery has excellent cycle performance and slow capacity decay. The sharp peaks indicate that the sulfur in the composite material has good reactivity and exhibits fast reaction kinetics.
[0034] Therefore, the present invention has the following advantages over the existing technology in the positive electrode of lithium-sulfur batteries:
[0035] 1. The present invention synthesizes heterostructure materials by vapor deposition. After calcination, a multilayer heterostructure is formed, with the Mo precursor as the substrate of the second phase. The formed heterostructure has more exposed active sites and a more complete reaction;
[0036] 2. The present invention reacts dopamine hydrochloride with molybdenum salt to induce the molybdenum precursor to form a lamellar structure, while accelerating the polymerization of dopamine to form a coating layer, so that the stability of the structure is effectively improved, and the carbonized dopamine can improve the conductivity of the heterostructure;
[0037] 3. The present invention adopts dopamine to coat the heterostructure. During the sulfurization process, dopamine is carbonized to obtain a nitrogen-doped carbon layer-coated heterostructure MoS2-MoO2, thereby increasing the redox rate and effectively reducing the shuttle effect of lithium polysulfide. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is the XRD pattern of NC / MSO obtained in step 2 of Example 1;
[0039] Figure 2This is the Raman graph of dopamine carbonized in NC / MSO in step 2 of Example 1;
[0040] Figure 3 This is the EDS image of NC / MSO in step 2 of Example 1;
[0041] Figure 4 The SEM image of the microstructure of NC / MSO in step 2 of Example 1;
[0042] Figure 5 Performing TEM test on the heterostructure interface of NC / MSO in step 2 of Example 1;
[0043] Figure 6 The cycling performance test diagram of the battery with S-NC / MSO, S-NC, S-NC / MO, and S-NC / MS positive electrodes at a current rate of 0.2C;
[0044] Figure 7 The S-NC / MSO in step 2 of Example 1 was used at a scan rate of 0.1 mV s -1 Cyclic voltammetry test was carried out under the following conditions;
[0045] Figure 8 The S-NC / MSO in step 2 of Example 1 was prepared at a scan rate of 0.1-0.5 mV s -1 Cyclic voltammetry test diagram under the following conditions:
[0046] Fig. 9 is the XRD pattern of NC / MO in step 2 of comparative example 1;
[0047] Fig.10 This is the SEM image of NC / MO in step 2 of comparative example 1;
[0048] Fig.11 is the XRD pattern of NC / MS in step 2 of comparative example 2;
[0049] Fig.12 This is the SEM image of NC / MS in step 2 of comparative example 2. DETAILED DESCRIPTION
[0050] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0051] Example 1
[0052] A method for preparing a nitrogen-doped carbon-coated molybdenum compound having a heterogeneous structure comprises the following steps:
[0053] Step 1, preparation of dopamine-coated molybdenum compound precursor, first, 0.64g of ammonium molybdate tetrahydrate is dissolved in a mixed solvent to obtain an ammonium molybdate solution, and at the same time, 0.3g of dopamine hydrochloride is placed in deionized water and ultrasonically obtained to obtain a dopamine solution; then, the mixing and stirring temperature is 60°C, the mixing and stirring time is 0.5h, and the dripping rate is 1mL min -1 The dopamine solution is slowly added dropwise to the ammonium molybdate solution under the condition of a dropping time of 15 minutes, and mixed and stirred to obtain a reaction solution. After the dropping is completed, the reaction solution is stirred and reacted under the conditions of a pH value of 8.5-9, a reaction temperature of room temperature, and a reaction time of 12 hours. After the reaction is completed, the obtained red suspension is filtered and freeze-dried to obtain a dopamine-coated molybdenum compound precursor PDA / Mo, referred to as PDA / Mo;
[0054] In step 1, the mixed solvent is a mixed solution of ethanol, deionized water and ammonia water, wherein the volume ratio of ethanol, deionized water and ammonia water is 20:10:1;
[0055] Step 2, preparation of nitrogen-doped carbon-coated molybdenum compound with heterostructure, under the condition of passing argon gas, with the mass ratio of PDA / Mo obtained in step 1 and thioacetamide TAA being 1:1, TAA is placed at the upwind port, PDA / Mo is placed at the downwind port, and the argon gas flow rate is 40 ml min -1 , heating rate is 5℃min -1 The calcination temperature is 800°C and the calcination time is 6 hours to obtain a nitrogen-doped carbon-coated molybdenum compound with a heterostructure NC / MoS2-MoO2, referred to as NC / MSO.
[0056] In order to verify the composition and crystal phase of NC / MSO obtained in step 2, XRD test was performed. The test results are shown in Figure 1 As shown, NC / MSO contains the characteristic peaks of both MoS2 and MoO2, and has good crystallinity.
[0057] In order to prove the graphitization degree of dopamine in NC / MSO obtained in step 2 after carbonization, Raman spectroscopy test was performed. The test results are shown in Figure 2 As shown in Figure 2, the carbon layer of NC / MSO has a defect peak D peak and a graphite peak G peak, and the peak height ratio is I D / I G =0.847. The test results show that NC / MSO has abundant internal defects and a high degree of graphitization, that is, it has excellent pore structure and good conductivity.
[0058] In order to verify the elemental composition of NC / MSO obtained in step 2, EDS test was performed. The test results are shown in Figure 3As shown, NC / MSO contains Mo, O, S, C and N elements at the same time, and the elements are evenly distributed. In addition, C and N elements are mainly concentrated in the edge area, which shows that the nitrogen-doped carbon layer is successfully coated.
[0059] In order to verify the microstructure of NC / MSO obtained in step 2, SEM test was performed. The test results are shown in Figure 4 As shown, the basic microstructure of NC / MSO is a spherical structure, which is composed of stacked lamellar structures.
[0060] In order to further verify the microstructure of NC / MSO obtained in step 2, TEM test was performed. Figure 5 As shown in the figure, NC / MSO has lattice fringes of MoO2 and MoS2 at the same time, and there is a heterogeneous interface, that is, a heterogeneous structure formed by MoO2 and MoS2. The reason is that when PDA / Mo is directly used as the growth substrate and MoS2 is prepared in situ, the distortion energy generated during the grain growth process is low, so they have similar tendencies, that is, MoO2 and MoS2 can nucleate and grow with each other to form a heterogeneous structure interface.
[0061] In order to prove the performance of NC / MSO as a positive electrode material for lithium-sulfur batteries, lithium-sulfur batteries are assembled for electrochemical performance tests, including constant current charge-discharge cycle tests and cyclic voltammetry performance tests. The specific method for assembling a lithium-sulfur battery is as follows: first, after grinding the sample to be tested with sulfur powder, a conventional melt diffusion method is used to obtain a carbon-sulfur composite material; then, the carbon-sulfur composite material is used as an active material, conductive carbon black is used as a conductive agent, polyvinylidene fluoride PVDF is used as a binder, and N-methylpyrrolidone NMP is used as a solvent. The active material, conductive agent, and binder meet a mass ratio of 8:1:1 to prepare a slurry; finally, the slurry is evenly coated on an aluminum foil to obtain an electrode sheet, and a conventional lithium-sulfur battery electrolyte is added in a glove box to assemble a button cell. In specific embodiment 1, the battery assembled with the NC / MSO obtained in step 2 as the positive electrode material for a lithium-sulfur battery is named S-NC / MSO.
[0062] The constant current charge-discharge cycle test results of S-NC / MSO are shown in Figure 6 As shown, under the condition of current rate of 0.2C, the initial discharge capacity is 1101mA hg -1 ; Under the condition of 200 cycles, the remaining discharge capacity is 878mAhg -1 , the capacity retention rate is 79.7%.
[0063] The constant scan rate cyclic voltammetry performance test results of S-NC / MSO are shown in Figure 7 As shown, at a scan rate of 0.1 mV s -1Under the same conditions, there are two groups of redox peaks, and the shape of the electrochemical window does not change significantly when the number of cycles is 3. The test results show that S-NC / MSO has good electrochemical reversibility and cycle stability.
[0064] The variable speed sweep cyclic voltammetry performance test results of S-NC / MSO are shown in Figure 8 As shown, at a scan rate of 0.1–0.5 mV s -1 Under these conditions, the shape of the electrochemical window did not change significantly, and the redox peak remained sharp. The test results showed that the polarization degree of S-NC / MSO was lower after the scan rate increased, which means that it has fast reaction kinetics.
[0065] In order to demonstrate the effect of heterogeneous structure on electrochemical performance, that is, the respective roles of MoO2 and MoS2 in the composite material, comparative examples 1 and 2 are provided to prepare composite materials containing only MoO2 and MoS2, respectively. At the same time, comparative example 1 is provided, in which MoO2 and MoS2 are not introduced, and the carbon material prepared by direct carbonization with PDA is used as the basic reference example.
[0066] Reference Example 1
[0067] A method for preparing a PDA-based carbon material, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 1, ammonium molybdate tetrahydrate is not added, and in the step 2, TAA is not added, so that the PDA-based carbon material can be obtained, and a battery assembled using the PDA-based carbon material as a positive electrode material for a lithium-sulfur battery is named S-NC.
[0068] The constant current charge-discharge cycle test results of S-NC are as follows Figure 6 As shown, under the condition of current rate of 0.2C, the initial discharge capacity is 950mA hg -1 ; Under the condition of 200 cycles, the remaining discharge capacity is 434 mAh g -1 , the capacity retention rate is 45.6%.
[0069] By comparing with Example 1, it can be seen that the simultaneous introduction of MoS2-MoO2 to form a heterogeneous structure, namely MoO2 and MoS2, has the function of significantly improving the capacity retention rate after cycling. The reason is that the heterogeneous structure that can be formed between MoS2-MoO2 has the following three specific functions:
[0070] Effect 1. MoO2 in the heterostructure has a polar effect on LiPSs and can effectively adsorb free LiPSs, thereby reducing the concentration of LiPSs in the electrolyte and inhibiting the shuttling of LiPSs;
[0071] Effect 2: MoS2 in the heterogeneous structure can improve the catalytic activity of LiPSs, accelerate the diffusion and transformation of LiPSs to Li2S, thereby reducing the loss of active substances and ultimately reducing capacity loss;
[0072] Effect 3: The heterostructure formed by MoO2 and MoS2 can form an asymmetric built-in electric field at the interface, thereby increasing the electron transmission rate and thus the reaction rate.
[0073] Therefore, in the reference example, when nitrogen-doped carbon is directly used as the positive electrode carrier material, due to the poor binding force of non-polar carbon materials to LiPSs with strong polarity, free LiPSs cannot be effectively anchored, resulting in a rapid decrease in the utilization rate of active materials, which seriously affects the cycle life of the battery.
[0074] Comparative Example 1
[0075] A method for preparing a composite material containing only MoO2, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 2, TAA is not added as a sulfur source to obtain a nitrogen-doped carbon-coated MoO2 composite material, and a battery assembled using the MoO2 composite material as a positive electrode material for a lithium-sulfur battery is named S-NC / MO.
[0076] In order to verify the composition and crystal phase of NC / MO obtained in step 2, XRD test was performed. The test results are shown in Fig. 9 As shown, NC / MSO only contains the characteristic peaks of MoO2 and has good crystallinity.
[0077] In order to verify the microstructure of NC / MO obtained in step 2, SEM test was performed. The test results are shown in Fig.10 As shown, the basic microstructure of NC / MO is a spherical structure with a rough surface.
[0078] The constant current charge-discharge cycle test results of S-NC / MO are shown in Figure 6 As shown in the figure, at a current rate of 0.2C, the initial discharge capacity is 942 mAh g -1 ; Under the condition of 200 cycles, the remaining discharge capacity is 536mAhg -1 , the capacity retention rate is 56.9%.
[0079] By comparing with the reference ratio, it can be seen that the introduction of MoO2 can effectively improve the capacity retention rate of lithium-sulfur batteries after cycling. The reason is as analyzed above. The introduction of MoO2 can only achieve effect 1. However, MoO2 has low catalytic activity for LiPSs and cannot improve the conversion efficiency of LiPSs. As the reaction proceeds, LiPSs accumulate too much at the negative electrode, resulting in reduced reaction kinetics and severe loss of active substances, that is, effect 2 cannot be achieved.
[0080] Further comparison with Example 1 shows that the introduction of MoO2 alone cannot form a heterostructure, and thus Effect 3 cannot be achieved.
[0081] Comparative Example 2
[0082] A method for preparing a composite material containing only MoS2, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 2, an excess of TAA is added as a sulfur source to obtain a nitrogen-doped carbon-coated MoS2 composite material, and a battery assembled using the MoS2 composite material as a positive electrode material for a lithium-sulfur battery is named S-NC / MS.
[0083] In order to verify the composition and crystal phase of NC / MO obtained in step 2, XRD test was performed. The test results are shown in Fig.11 As shown, NC / MSO only contains the characteristic peaks of MoS2 and has good crystallinity.
[0084] In order to verify the microstructure of NC / MO obtained in step 2, SEM test was performed. The test results are shown in Fig.12 As shown, the basic microstructure of NC / MS is a spherical structure, which presents a flake structure.
[0085] The constant current charge-discharge cycle test results of S-NC / MS are shown in Figure 6 As shown in Figure 2, at a current rate of 0.2C, the initial discharge capacity is 963 mAh g -1 ; Under the condition of 200 cycles, the remaining discharge capacity is 598mAhg -1 , the capacity retention rate is 62.1%.
[0086] By comparing with the reference ratio, it can be seen that the introduction of MoS2 alone can effectively improve the initial specific capacity of lithium-sulfur batteries. The reason is as analyzed above. The introduction of MoS2 can only achieve effect 2. However, MoS2 has a small adsorption effect on LiPSs and a low adsorption energy. It cannot anchor LiPSs in the continuous reaction. When the concentration of LiPSs in the electrolyte is too high, the catalytic sites of MoS2 are occupied, thereby reducing the catalytic activity, resulting in a decrease in reaction kinetics and battery cycle stability, that is, effect 1 cannot be achieved.
[0087] Further comparison with Example 1 shows that the introduction of MoS2 alone cannot form a heterostructure, and thus Effect 3 cannot be achieved.
[0088] From Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the technical effect obtained by simultaneously introducing MoO2 and MoS2 to form a heterogeneous structure cannot be achieved by introducing MoO2 and MoS2 separately. The reason is that in addition to having different effects on LiPSs, the built-in battery generated between the two substances can quickly realize the complete reaction process of adsorption-diffusion-conversion on the interface of LiPSs, which can effectively reduce the loss of active substances, thereby improving the cycle stability of the battery.
Claims
1. A nitrogen-doped carbon-coated molybdenum compound having a heterogeneous structure, characterized in that: Using ammonium molybdate tetrahydrate as the molybdenum source and thioacetamide TAA as the sulfur source, firstly, the polydopamine-coated precursor PDA / Mo is obtained by stirring precipitation, and then the precursor and TAA are calcined and partially sulfurized to obtain a nitrogen-doped carbon-coated molybdenum compound NC / MoS2-MoO2 with a heterogeneous structure, referred to as NC / MSO.
2. The nitrogen-doped carbon-coated molybdenum compound having a heterostructure according to claim 1, characterized in that: The NC / MSO is composed of MoO2 and MoS2, and a heterogeneous interface exists between MoO2 and MoS2.
3. The nitrogen-doped carbon-coated molybdenum compound having a heterostructure according to claim 1, characterized in that: The carbon layer of the NC / MSO has a defect peak D peak and a graphite peak G peak, and the peak height ratio I D / I G =0.847; the microstructure of NC / MSO is a spherical structure formed by stacking layers, and the surface of the layers is rough; there are obvious gaps between the layers.
4. A method for preparing a nitrogen-doped carbon-coated molybdenum compound having a heterogeneous structure, characterized in that The following steps are involved: Step 1, preparation of a dopamine-coated molybdenum compound precursor, first, dissolving ammonium molybdate tetrahydrate in a mixed solvent to obtain an ammonium molybdate solution, and at the same time, placing dopamine hydrochloride in deionized water and ultrasonically obtaining a dopamine solution; then, under certain conditions, slowly dropping the dopamine solution into the ammonium molybdate solution for mixing and stirring to obtain a reaction solution, after the dropwise addition is completed, under certain conditions, stirring the reaction solution for reaction, after the reaction is completed, filtering the obtained red suspension and freeze-drying it to obtain a dopamine-coated molybdenum compound precursor PDA / Mo, referred to as PDA / Mo; Step 2, preparation of nitrogen-doped carbon-coated molybdenum compounds with heterostructures. Under certain conditions, the PDA / Mo obtained in step 1 and thioacetamide TAA meet a certain mass ratio, and TAA and PDA / Mo are calcined to obtain nitrogen-doped carbon-coated molybdenum compounds with heterostructures NC / MoS2-MoO2, referred to as NC / MSO.
5. The preparation method according to claim 4, characterized in that: In the step 1, the mass ratio of ammonium molybdate tetrahydrate to dopamine hydrochloride is 2.13:1; In the step 2, the mass ratio of PDA / Mo to thioacetamide TAA is 1:
1.
6. The preparation method according to claim 4, characterized in that: In the step 1, the mixed solvent is a mixed solution of ethanol, deionized water and ammonia water, wherein the volume ratio of ethanol, deionized water and ammonia water is 20:10:1; In step 1, the mixing and stirring conditions are as follows: adding dropwise under stirring, the mixing and stirring temperature is 50-60°C, the mixing and stirring time is 0.5-1h, and the dropping rate is 1mLmin -1 The addition time is 10-15min; In step 1, the stirring reaction conditions are: pH value is 8.5-9, reaction temperature is room temperature, and reaction time is 10-12h.
7. The preparation method according to claim 4, characterized in that: In step 2, the calcination conditions are as follows: TAA is placed at the upwind port, PDA / Mo is placed at the downwind port, and the argon gas flow rate is 40-60 ml min -1 , heating rate is 2-5℃min -1 , the calcination temperature is 700-800℃, and the calcination time is 3-6h.
8. The nitrogen-doped carbon-coated molybdenum compound having a heterostructure according to claim 1, characterized in that: When used as a positive electrode material for lithium-sulfur batteries, the initial discharge capacity is 1100-1200 mAh g at a current rate of 0.2C. -1 .
9. The nitrogen-doped carbon-coated molybdenum compound having a heterostructure according to claim 1, characterized in that: When used as a positive electrode material for lithium-sulfur batteries, the residual discharge capacity is 800-900 mAh g under the condition of 200 cycles. -1 , the capacity retention rate is 75-80%.
Citation Information
Patent Citations
Zinc sulfide nano-belt, preparation and application thereof in preparing anode material of lithium sulfur battery
CN106927498A
Simple construction method of nano carbon shell loaded molybdenum-based heterojunction and application of nano carbon shell loaded molybdenum-based heterojunction in lithium-sulfur battery
CN113113570A
Microwave preparation method and application of graphene / molybdenum sulfide / molybdenum oxide heterostructure catalyst
CN113368877A
MoS2-MoOx composite material for negative electrode of lithium ion capacitor as well as preparation method and application of MoS2-MoOx composite material
CN117747313A
Doped carbonaceous materials for photocatalytic removal of pollutants under visible light, making methods and applications of same
US20190015818A1